COVER CROPS AND THEIR RELATIONSHIP WITH THE QUALITATIVE AND QUANTITATIVE ATTRIBUTES OF SOYBEANS - Bellinasso, Alex Vinicius; Carvalho, Ivan Ricardo; Silva, José Antonio Gonzalez da; Moura, Natã Balssan; Hutra, Danieli Jacoboski; Loro, Murilo Vieira; Bubans, Valéria Escaio; Lautenchleger, Francine (REVISTA DE AGRICULTURA, 2021)
The work aims to evaluate the effects of soil cover and soybean cultivars on the qualitative and quantitative attributes of soybeans. The experiment was conducted Giruá – RS, with experimental design was a randomized factorial block design, with two cover crops x seven soybean cultivars, disposed in three repetitions. Agricultural characteristics and nutritional attributes of soya were evaluated. The different coverings influenced the soybean performance for the main variables studied, grain yield was maximized in the coverage of Raphanus sativus + Avena strigosa for the cultivar DM 57I52 IPRO, and the greenish grain levels were lower, consequently increasing the percentage of oil content for that same coverage. The components of variance and genetic parameters show that grain yield was influenced by 56% due to the effects of cultivars and 44% coming from the soil cover used.